Home Availability and the Impact of Weekly Stressful Events Are Associated with Fruit and Vegetable Intake among African American and Hispanic/Latina Women - Tracey A. Ledoux; Scherezade K. Mama; Daniel P. O'Connor; Heather Adamus; Margaret L. Fraser; Rebecca E. Lee (Journal of Obesity)
Background. Mediating and moderating variables may interfere with the association between neighborhood availability of grocery stores (NAG) and supermarkets (NAS) and fruit and vegetable (FV) intake. Objective. The purpose of this study was to test mediation of home availability of FV (HAFV) and moderation of impact of weekly stressful events (IWSE) on the association between NAG and NAS with FV consumption among African American (AA) and Hispanic/Latina (HL) women. Methods. Three hundred nine AA and HL, 25–60 year old women in the Health Is Power (HIP) randomized controlled trial completed validated measures of HAFV, IWSE, and FV intake at baseline. Trained field assessors coded NAG and NAS. Institutional Review Board approval was obtained. Results. NAG and NAS were not associated with FV intake or HAFV, so HAFV was not a mediator. HAFV (std. Beta = .29, P<0.001) and IWSE (std. Beta = .17; P<0.05) were related to FV intake (R2  =0.17; P<0.001), but IWSE was not a moderator. Conclusion. Increasing HAFV and decreasing the IWSE should increase FV consumption. The extent to which the neighborhood environment is related to the home food environment and diet, and the mechanisms for the association between IWSE and diet should be examined in future research.